Chapter 34 Affective Witnessing of the Hijab A Self-Inflicted Trauma - Abdel-Fadil, Mona (Taylor & Francis, 2023)
The hijab has triggered affects for centuries. It has sparked narratives of "saving" Muslim women from the shackles of Muslim men and Islam. In recent years, we have seen several examples of individuals and collectives who experience the mere sighting of the hijab as intolerable. Here, I take a closer look at the affects of "awayness" that move through the hijab in contemporary Western contexts, and how these affects are performed, heightened, and intensified online. Drawing on a decolonial approach to affect and extensive ethnographic research, I argue that collectives who are deeply immersed in the heightened and intensified affective engagement against the hijab, spell out their own symbolic death. By continuously affectively witnessing the hijab, and triggering affects such as despair, anger, outrage, sorrow, and grief, it becomes a self-inflicted trauma, perceived as unbearable. Thus, affective witnessing shifts the focus from ascribed-victimization of Muslim women to self-victimization. And, the affective witnesses of hijab emerge as the "true victims" of hijab.